Describing the Wavefront Aberrations of the Hexagonal Aperture Using Modified Zernike Polynomials - Abood, Loay; Al-Hilly, Shatha; Hassan, Raaid (Iraqi Journal of Science, 2023)
The concept of the optical telescope is the primary mirror design, the Next Generation Segmented Optical Telescope (NGST) with hexagonal segment of spherical primary mirror can provide a 3 arc minutes field of view. Extremely Large Telescopes (ELT) in the 100m dimension would have such unprecedented scientific effectiveness that their construction would constitute a milestone comparable to that of the invention of the telescope itself and provide a truly revolutionary insight into the universe. The scientific case and the conceptual feasibility of giant filled aperture telescopes was our interested. Investigating the requirements of these imply for possible technical options in the case of a 100m telescope. For this telescope the considerable interest is the correction of the optical aberrations for the coming wavefront, the modified Zernike polynomials for hexagonal aperture were used to describe the wavefront aberrations and to predict the initial state for the adaptive optics corrections.